Effect of Modisco-Cookies Combined with Auriculopuncture therapy on Increment of Body Weight - Latifah, Maasyitoh Sari; Puruhito, Edith Frederika; Budhy, Theresia Indah; Azis, Zulfikran Moh Rizki (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Being underweight is a common problem in developing countries, including Indonesia, that may cause infections, including viral ones. The solution to this problem is to provide Modisco cookies and auriculopuncture therapy with seed-pressing methods. Auriculopuncture is a traditional Chinese therapy using the seed-pressing method at the auricular point stimulating to relieve other body pathologies. While Modisco cookies have energy-dense, high- calories, digestible cookies that aim to help accelerate weight gain. This study aims to determine the effect of Modisco cookies compared to a combination of Modisco cookies with auriculopuncture on the increase of body weight among male adolescents. This study observed 22 male teenagers with low body weight for three weeks. The subjects are categorized into two treatment groups: (1) the Modisco cookies group and (2) the combination of Modisco cookies and the auriculopuncture treatment group every day for three weeks (26 days). This study compared the mean of the pretest and posttest of the weight changes using a T-test. Furthermore, the average weight changes between the two groups were compared using Manova repeated measured test. The Modisco cookies have nutrient-dense and easy to digest, while Auriculopuncture may stimulate to a certain point in the ear. The hypothalamus has a role in the production of the ghrelin hormone. The therapy may increase hormone appetite and reduce the use of fat reserves. It may increase the body weight of underweight adolescents significantly (p=0.00). A combination of Modisco cookies and auriculopuncture therapy gave a significant increase in adolescent body weight compared to modisco cookies.